PENDUGAAN EROSI DAN ANALISIS TINGKAT BAHAYA EROSI DENGAN METODE UNIVERSAL SOIL LOSS EQUATION (USLE) DI BERBAGAI PENGGUNAAN LAHAN DI WILAYAH KECAMATAN PUJON - Siswanto; Kemal Wijaya; Muhammad (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[PREDICTING SOIL EROSION AND EROSION HAZARD LEVEL IN VARIOUS LAND-USES IN THE AREA OF PUJON SUB-DISTRICT USING THE UNIVERSAL SOIL LOSS EQUATION (USLE) MODEL] The area of Pujon Sub-District is vulnerable for soil erosion due to hilly tropography. Therefore, the study aimed to predict the rate of erosion and erosion hazard level in various land uses in the Pujon district. Soil erosion was predicted by using data on soil sample at depths of 0-30 cm and 30-60 cm in each land-use/cover with three repetitions. Soil sampling was done by using purposive sampling method. the collected data were analysed using software ArcGIS. Results show that the predicted average soil erosion with a very light erosion severity was 0,02 - 3,39 ton/ha/year occurring in land-uses/covers of H1, H2, H3, H4 and K2. Whereas, the predicted soil erosion levels for the medium and heavy soil erosion severity were 0,95 - 15,48 ton/ha/year and 15,48 - 28,17 ton/ha/year occurring in the land-use units of T1, T2, and K4 and in the land-use units of T3 and T4, respectively. Thus, the erosion hazard levels in the Area of Pujon Sub-District are dominated by light and moderate erosion categories